Novel Cell-Penetrating Peptides Derived From Scaffold-Attachment- Factor A Inhibits Cancer Cell Proliferation and Survival - Puvvula, Pavan Kumar; Moon, Anne M. (Frontiers in Oncology, 2021)
Scaffold-attachment-factor A (SAFA) has important roles in many normal and pathologic cellular processes but the scope of its function in cancer cells is unknown. Here we report dominant-negative activity of novel peptides derived from the SAP and RGG-domains of SAFA and their effects on proliferation, survival and the epigenetic landscape in a range of cancer cell types. The RGG-derived peptide dysregulates SAFA binding and regulation of alternatively spliced targets and decreases levels of key spliceosome proteins in a cell-type specific manner. In contrast, the SAP-derived peptide reduces active histone marks, promotes chromatin compaction, and activates the DNA damage response and cell death in a subset of cancer cell types. Our findings reveal an unprecedented function of SAFA-derived peptides in regulating diverse SAFA molecular functions as a tumor suppressive mechanism and demonstrate the potential therapeutic utility of SAFA-peptides in a wide range of cancer cells.